A Simplified and Effective Method for Generation of Experimental Murine Periodontitis Model - Li, Danfeng; Feng, Yi; Tang, Hang; Huang, Lijia; Tong, Zhongchun; Hu, Cheng; Chen, Xiaodan; Tan, Jiali (Frontiers in Bioengineering and Biotechnology, 2020)
Periodontitis, a common disease that can lead to bone destruction, periodontal attachment loss, and tooth loss, is the major cause for oral tissue engineering. Experimental periodontitis is a suitable disease-model for studying bone regeneration and the potential therapeutic role of biomaterials on periodontal tissue engineering, as this in vivo model could be employed to mimic the natural host response under bacteria-caused oral pathological environments. Although large animals with ligature-induced periodontitis have mostly been used for experiments, a mouse model is a better choice because of numerous advantages. Inserting ligature threads through the interproximal space between the teeth is the key step to establishing a periodontitis model, and it is easy to achieve in large animals, but difficult in mice due to the limited operating space. In this work, we provide a new and proven approach for periodontitis induction in mice using C+ nickel-titanium root canal files and stainless-steel ligature wires. The validity of this method was assessed by evaluating alveolar bone loss via micro-CT and detecting periodontal inflammation by histological staining and qPCR after the treatments. Progressive alveolar bone loss was observed from day 3 after the ligature-placement. Infiltration and accumulation of F4/80+ macrophage was also detected. In accordance with the histological results, there was upregulation of the expression levels of the inflammatory genes Il1β, Tnf-α, and Il6 in gingival tissues isolated from ligation sites. Our results suggest that this novel method is expected to resolve the difficulty of ligature-placement in mice and consequently contribute to further use of a mouse model for studying the pathological mechanisms of periodontitis and developing potential periodontal tissue regeneration strategies. C+ files, which are made of nickel-titanium, are tough, elastic, and sufficiently thin to pass through the interproximal space between the teeth after pre-bending to form an appropriate angle, thus providing an access for ligature wire insertion. As a common tool in the dental clinic, it is familiar to researchers of oral biology, and can provide the feasibility for wide application of our method.